1998
DOI: 10.1039/a705920e
|View full text |Cite
|
Sign up to set email alerts
|

Platinum concentrations in urban road dust and soil, and in blood and urine in the United Kingdom†

Abstract: Increasing Pt concentrations from vehicle catalysts have been reported from a number of countries. Analysis of Pt and Pd in soils and road dusts taken from areas of high and low traffic flows in SE England show concentrations of Pt in the range < 0.30-40.1 ng g-1 and Pd in the range < 2.1-57.9 ng g-1. Higher concentrations of Pt are associated with high traffic densities. Samples taken from streets of lower traffic flows were found to contain the lower concentrations of the ranges. Pilot studies of Pt concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
54
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 13 publications
(22 reference statements)
6
54
0
5
Order By: Relevance
“…Emission of soluble and therefore possibly toxic platinum is estimated to be about 1% (Artelt et al, 1999 ). Occupationally related uptake of platinum by inhalation from car traffic seems to be of no relevance as far as internal exposure is concerned (Begerow et al, 1999a;Farago et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Emission of soluble and therefore possibly toxic platinum is estimated to be about 1% (Artelt et al, 1999 ). Occupationally related uptake of platinum by inhalation from car traffic seems to be of no relevance as far as internal exposure is concerned (Begerow et al, 1999a;Farago et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the analytical method applied and the study group, different levels of platinum in urine have been reported (Table 1 ) (Weber et al, 1991;Ensslin et al, 1994;Schierl et al, 1994Schierl et al, , 1998Schramel et al, 1995;Begerow et al, 1996Begerow et al, , 1997Begerow et al, , 1999aFarago et al, 1998;Philippeit and Angerer, 1999;Schierl, 2001 ). To date, it is not known to what extent different exposure pathways and the chemical species influence the platinum concentration in environmentally exposed humans.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations